Comprehensive analysis of the results of surgical treatment of patients with degenerative diseases of the lumbar spine using rigid fixation systems - A. E. Krivoschein; V. P. Konev; S. V. Kolesov; S. A. Erofeev; S. N. Moskovskiy; V. A. Byvaltsev (Acta Biomedica Scientifica, 2022)
Introduction. According to the literature, the development of adjacent-level syndrome 10 years after posterior rigid stabilization is noted in 6.7–80 % of patients, of which 24 % require revision surgery.The aim: to conduct a comprehensive analysis of the results of surgical treatment of patients with degenerative diseases of the lumbar spine using rigid fixation systems.Materials and methods. A multicenter retrospective study of the results of surgical treatment of 268 patients with degenerative-dystrophic diseases of the lumbar spine, who underwent mono- or bisegmental decompression-stabilizing intervention with the implementation of the TLIF (Transforaminal Lumbar Interbody Fusion) technique and open transpedicular rigid fixation, was conducted. The study included radiography, MRI and CT (in 2-energy mode) of intervertebral discs and isolated facet degeneration of the upper adjacent level.Results and discussion. The combination of the initial degeneration of the adjacent spinal motion segment in the form of disc degeneration of grade III and higher according to Pfirrmann with threshold values of the density of the outer cartilaginous plate from 161.7 ± 18.8 to 164.8 ± 14.2 HU, the density of the outer facet – from 702.43 ± 12.3 to 713.65 ± 13.6 HU and the density of the inner facet – from 580.5 ± 11.6 to 582.1 ± 15.1 HU, as well as with signs of segmental instability of the adjacent segment can be considered as risk factors for the development of its degeneration. With the progression of degeneration of the upper intervertebral disc, revision interventions were performed within 12–60 months after surgery.Conclusion. Bisegmental stabilization with signs of initial degeneration in the intervertebral disc and facet joints in the upper segment has proven its clinical and instrumental effectiveness in the period of 36 months and reduces the risks of developing degenerative disease of the adjacent disc.